Kiai's Leadership in Improving the Quality of Education at the Miftahul Huda 453 Banyumas Pringsewu Islamic Boarding School - Ulumuddin, Bahrul; Salamun, Slamun (Civiliza Publishing, 2025)
Islamic boarding schools are the most varied Islamic educational institutions, because they depend on the dominant Kiai leadership as the central figure and basic element of Islamic boarding schools. Kiai leadership, which is varied and carried out from generation to generation, is a particular problem in Islamic boarding schools. Apart from that, the focus on religious knowledge and lack of openness to modernization makes Islamic boarding schools less attractive to modern society. The quality of education that is used as a public opinion when choosing a school means that Islamic boarding schools need to improve so that they can survive in the modern era. Therefore, there is a need for a Kiai leadership role in improving the quality of education in Islamic boarding schools. This research aims to describe the leadership role of Kiai in improving the quality of education at the Miftahul Huda 453 Islamic Boarding School and identify obstacles in implementing the Kiai's leadership role in improving the quality of education at the Miftahul Huda 453 Islamic Boarding School. The approach used in this research is qualitative research with the type of research being field. with a phenomenological approach. Meanwhile, using observation data collection techniques, document studies and interviews. The data analysis techniques use data reduction, presentation and verification. The researchers found that: Kiai leadership applies a democratic leadership style in terms of its authority, and a paternalistic style in terms of its characteristics, and it can be seen that there is an autocratic style indirectly when seen from the way it influences subordinates. Kiai's leadership role when drawn from E. Mulyasa's theory is: as educator, manager, leader, innovator, supervisor, motivator. The kiai's influence as a central figure in the Islamic boarding school is responsible for ensuring the quality of education as well as changes and developments in accordance with the goals of the Islamic boarding school.